2021
DOI: 10.1155/2021/9274964
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Whole-Body Vibration Exercise on Anticipatory Delay of Core Muscles in Patients with Nonspecific Low Back Pain

Abstract: Objective. The objective of this study is to determine the effect of whole-body vibration (WBV) exercise on the anticipatory delay of core muscles in nonspecific low back pain (NSLBP) patients. Methods. Forty participants with NSLBP were randomly divided into the WBV group and the control group. The sEMG signals of deltoid, erector spines (ES), multifidus (MF), rectus abdominis (RA), and transversus abdominus/internal oblique muscles (TrA/IO) were recorded before and after the intervention in the weight-shifti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Abnormal trunk neuromuscular control alterations, such as decreased muscular endurance, muscle strength, and lumbar proprioception, are positively correlated with pain severity and pain-related dysfunction in patients with NCLBP [ 48 ]. APA, an important strategy of posture control, have also been reported to be related with the development of non-specific chronic low pain [ 49 , 50 ]. It has been demonstrated that an increasing delay in the latency of external oblique muscle activation is accompanied by an increased Oswestry Disability Index score in patients with chronic low back pain, which occurs when performing a rapid arm-raising task [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal trunk neuromuscular control alterations, such as decreased muscular endurance, muscle strength, and lumbar proprioception, are positively correlated with pain severity and pain-related dysfunction in patients with NCLBP [ 48 ]. APA, an important strategy of posture control, have also been reported to be related with the development of non-specific chronic low pain [ 49 , 50 ]. It has been demonstrated that an increasing delay in the latency of external oblique muscle activation is accompanied by an increased Oswestry Disability Index score in patients with chronic low back pain, which occurs when performing a rapid arm-raising task [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…An individualized frequency protocol 3,4 required the participants to stand barefoot with knees flexed to approximately 15 degrees 2 on a 0.8 x 1.01m synchronous vibration plate (Pneu-VibePro, Sandpoint, ID) vibrating with a peak-to-peak amplitude of 2mm. Participants completed a baseline (no vibration) trial immediately followed by 10 seconds of vibration at randomized frequencies of 20,25,30,35,40,45, 50 or 55 Hz (1.61 g -12.2 g). Between each vibration exposure four-minutes of rest was provided to limit the effects of fatigue or crossover from the previous vibration exposure resulting in eight vibration exposures during the first session.…”
Section: Methodsmentioning
confidence: 99%
“…As such, the purpose of this study was to examine the effect of an individualized frequency WBV training program on GRFs, lower limb mechanics and the differences associated with the sex of the individual during the landing phase of a drop jump. It was hypothesized that GRFs, loading rates, valgus knee moment and valgus knee angles would show an acute decrease in non-sedentary individuals following an individualized frequency WBV training session as a result of the potential changes in proprioception following the vibration exposure 23,25 . Additionally, it was hypothesized that WBV would not differentially alter performance based on the individual's sex.…”
Section: Introductionmentioning
confidence: 99%
“…The total number of patents in existence today is enormous and increasing quickly, yet there are very few significant patents that are essential to the advancement of the industrial technology system. Therefore, identifying the key core patents from the huge number of patents is critical for comprehending present technology levels and properly anticipating technological development trends [ 16 ]. In present research, the following approaches for patent identification are often used: single index method, combination index method, index system method, patent information visualization, and so on.…”
Section: Literature Reviewmentioning
confidence: 99%